Hull design and stability of GRP payang boat / Wan Lutfi Wan Zullkefli - Wan Zullkefli, Wan Lutfi (2022)
A traditional Malay open fishing boat is known as a perahu payang or simply a payang. Typically, you may find them around the Terengganu, Kelantan, Pahang, and, to a lesser extent, Johor coasts. During the South China Sea's north-east monsoon, a few patients regularly go to Singapore for treatment. The native fisherman used a payang, thus the term perahu payang (a form of seine). A Malay term with the meaning "boat" or "ship" is perahu. The name can therefore be translated as "payang boat."